1979
DOI: 10.1042/cs0560585
|View full text |Cite
|
Sign up to set email alerts
|

Effects of an Orally Active Converting-Enzyme Inhibitor, SQ 14225, on Pressor Responses to Angiotensin Administered into the Brain Ventricles of Spontaneously Hypertensive Rats

Abstract: 1. Two hours after oral feeding of normotensive Wistar Kyoto rats with the converting-enzyme inhibitor SQ 14225 (1 and 10 mg/kg), an increase of angiotensin I plasma concentrations from 892 +/- 113 to 1660 +/- 167 and 2951 +/- 405 pg/ml was observed. 2. Administration of SQ 14225 with the drinking fluid overnight suppressed the pressor responses to intravenous angiotensin I, although the blood pressure increase after intravenous angiotensin II was not altered in normotensive and spontaneously hypertensive rats… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

1981
1981
2000
2000

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…This explanation does not account, however, for the failure of intracerebroventricular [Sar'/Thr'jAng II to lower blood pressure in the studies of Bruner et al 5 and Berecek et al 7 or for the failure of captopril to lower blood pressure in the study of Mann et al 8 ; and in the present study, we demonstrated blockade of the pressor response to intracerebroventricular Ang II with intracerebroventricular DuP 753. In our opinion, the absence of the metabolite does not explain why clearly demonstrable blockade of brain Ang II did not lower blood pressure in these studies.…”
Section: Discussionmentioning
confidence: 39%
“…This explanation does not account, however, for the failure of intracerebroventricular [Sar'/Thr'jAng II to lower blood pressure in the studies of Bruner et al 5 and Berecek et al 7 or for the failure of captopril to lower blood pressure in the study of Mann et al 8 ; and in the present study, we demonstrated blockade of the pressor response to intracerebroventricular Ang II with intracerebroventricular DuP 753. In our opinion, the absence of the metabolite does not explain why clearly demonstrable blockade of brain Ang II did not lower blood pressure in these studies.…”
Section: Discussionmentioning
confidence: 39%
“…36 Similarly, converting enzyme inhibition attenuated pressor responses to centrally administered Al. 41 These reports make it probable that ACE is involved in the physiological function of central angiotensin-containing neurons. It is likely that the activity of these neurons might be altered in states of altered sodium appetite or fluid homeostasis such as occurs with changes in dietary sodium intake.…”
Section: Intracerebroventricular Infusion Of Angiotensin IImentioning
confidence: 99%
“…4 Further, acute or chronic intracerebroventricular administration of either saralasin or captopril at doses that are minimally effective in lowering blood pressure when given intravenously markedly reduces blood pressure in adult SHR and attenuates the development of hypertension in young SHR but has a minimal effect on blood pressure in age-matched WKY rats. 5 -' 1 Previous studies have demonstrated that an anterior hypothalamic knife cut that isolates the anterior hypothalamic area (AHA) from other cardiovascular control areas in the brain stem and hypothalamus eliminates both the pressor response to centrally administered Ang II and the central component of the pressor response to intravenous Ang II in normotensive rats. 12 Thus, neurons in AHA appear to participate in the centrally mediated pressor response to exogenous Ang II.…”
mentioning
confidence: 99%